Radiation emitting device - (:unkn) unknown (My University, 2013)
A radiation emitting device comprising a first electrode, which emits first charge carriers having a first charge during operation, a first charge carrier transporting layer, which comprises a fluorescent substance, a second charge carrier transporting layer, which contains a phosphorescent substance, and a second electrode, which emits second charge carriers having a second charge during operation, wherein during operation the second charge carrier transporting layer is largely free of first charge carriers.
Keywords: Radiation emitting device; Processes Or Apparatus Peculiar To Manufacture Or Treatment Of Such Devices Or Of Parts Thereof (257/E51.001); Organic Solid State Devices; Emitted radiation; Organic Semiconductor Material (257/40); H01L 35/24 (20060101)